The peculiarities of heat transfer in CO2 and N2O solids at low temperatures: Classical Cryocrystals - Sumarokov, V.V.; Stachowiak, P.; Jeżowski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The thermal conductivities of CO2 and N2O solids have been investigated in the low-temperature range 1–40 K. The thermal conductivities of CO2 and N2O are large compared with those of simple molecular crystals such as N2, CO, or O2 in the whole investigated temperature range. Analysis of the experimental data by the Callaway method shows that relatively large size of crystalline grains, low density of dislocations and weak phonon–phonon interaction might be the reasons for the good thermal conduction in these crystals at temperatures near the maxima. A comparison between calculated values of the intensity of normal phonon scattering processes and experiment gives evidence that in N2O there is an additional (in comparison with CO2) giant scattering of phonons. This scattering is described in the frameworks of soft potential model by the resonance phonon scattering on tunnel states and low-energy vibratons.